2022
DOI: 10.1007/s40843-021-1913-4
|View full text |Cite
|
Sign up to set email alerts
|

Binder-free S@Ti3C2Tx sandwich structure film as a high-capacity cathode for a stable aluminum-sulfur battery

Abstract: The rechargeable aluminum-sulfur (Al-S) battery is a promising alternative-energy storage device with high energy density and made of cheap raw materials. However, Al-S batteries face several obstacles, especially the shuttle effect. Herein, a binder-free S@Ti 3 C 2 T x sandwich structure film with uniform sulfur dispersion was designed. The two-dimensional (2D) layered material Ti 3 C 2 T x not only has the function of binder and conductive agent but also is a promising host for sulfur anchoring. As a result,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…Table 1 lists the highest stepwise relative free energy increase, that is, the reaction energy barrier (E a ), which was in the range of 0.23−4.26 eV for different SA@Ti 3 C 2 O 2 nanosheets. Compared to the observed pure Ti 3 C 2 O 2 nanosheets (E a = 1.12 eV), 10 Cr@Ti 3 C 2 O 2 and Zr@Ti 3 C 2 O 2 showed similar E a values, indicating that there was little difference in their required overpotential. Most noticeably, Y@Ti 3 C 2 O 2 , Rh@ Ti 3 C 2 O 2 , Tc@Ti 3 C 2 O 2 , Mo@Ti 3 C 2 O 2 , and Nb@Ti 3 C 2 O 2 had E a values of 0.23, 0.51, 0.80, 0.99, and 1.05 eV, indicating that they were expected to further decrease the minimal overpotential of the electrochemical process compared with pure Ti 3 C 2 O 2 nanosheets.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Table 1 lists the highest stepwise relative free energy increase, that is, the reaction energy barrier (E a ), which was in the range of 0.23−4.26 eV for different SA@Ti 3 C 2 O 2 nanosheets. Compared to the observed pure Ti 3 C 2 O 2 nanosheets (E a = 1.12 eV), 10 Cr@Ti 3 C 2 O 2 and Zr@Ti 3 C 2 O 2 showed similar E a values, indicating that there was little difference in their required overpotential. Most noticeably, Y@Ti 3 C 2 O 2 , Rh@ Ti 3 C 2 O 2 , Tc@Ti 3 C 2 O 2 , Mo@Ti 3 C 2 O 2 , and Nb@Ti 3 C 2 O 2 had E a values of 0.23, 0.51, 0.80, 0.99, and 1.05 eV, indicating that they were expected to further decrease the minimal overpotential of the electrochemical process compared with pure Ti 3 C 2 O 2 nanosheets.…”
mentioning
confidence: 72%
“…12,32,33 The process of charging and discharging proceeding through the formation of Al 2 S n can be described as eqs 3 and 4. 10,22 + + 2Al 14AlCl 8Al Cl 6e 4 2 7…”
mentioning
confidence: 99%
“…The reason why MXene is functionalized that bare Ti 2 C 3 will be terminated on the surface by S which means carrying out a reversible reaction impossibly. [75][76][77] Similarly, in Lv et al works, sulfate formed by the reaction of dissociated -OH with S is identified through a peak at 532.0 eV of SO 4 2À , which restrains the dissolution of Reproduced by permission. 74 Copyright 2019, American Chemical Society.…”
Section: Doping Mechanism Of Mxene/sulfur Compositementioning
confidence: 93%
“… 73 The DFT calculation proves that S/O better anchors the polysulfides and S. To analyze the effect of functional groups on the kinetics of nucleation and decomposition of Li‐S, diffusion barriers are sorted and it is found that the minimum Li + diffusion barriers on Ti 3 C 2 O 2 and Ti 3 C 2 S 2 are fairly low, while the boding between Li + and N greatly hindering the dynamics (Figure 3D). The reason why MXene is functionalized that bare Ti 2 C 3 will be terminated on the surface by S which means carrying out a reversible reaction impossibly 75‐77 . Similarly, in Lv et al works, sulfate formed by the reaction of dissociated ‐OH with S is identified through a peak at 532.0 eV of SO 4 2− , which restrains the dissolution of LiPSs 53 .…”
Section: Doping Mechanism Of Mxene/sulfur Compositementioning
confidence: 94%
“…[8,[10][11][12] However, most reported Al-S batteries were driven by the reversible reduction of S, which only deliver low discharge voltages (≈0.4-1.0 V, theoretical voltage is 1.25 V vs Al 3+ /Al) with large voltage hysteresis at room temperature. [13][14][15][16][17][18][19][20][21][22][23] Therefore, it is of high merit to innovate the Al-S electrochemistry to significantly lift the discharge voltage for enhanced energy density. [12,19] The reversible electrochemical oxidation of S with high intrinsic electromotive force can provide such an opportunity.…”
mentioning
confidence: 99%